2020
DOI: 10.1186/s42492-020-00057-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of augmented reality in medicine, retail, and games

Abstract: This paper presents a detailed review of the applications of augmented reality (AR) in three important fields where AR use is currently increasing. The objective of this study is to highlight how AR improves and enhances the user experience in entertainment, medicine, and retail. The authors briefly introduce the topic of AR and discuss its differences from virtual reality. They also explain the software and hardware technologies required for implementing an AR system and the different types of displays requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(54 citation statements)
references
References 77 publications
(76 reference statements)
0
37
0
Order By: Relevance
“…A limitation of the study is the small sample size; future study could replicate this contribution involving more participants with the aim of generalizing results to other countries and healthcare contexts as well. For example, a recent systematic review and meta-analysis by Parekh, Patel, Patel, and Shah [43] showed the relevant application of augmented reality also in the medical area. Similarly, Pulijala and colleagues [44] The technologies used in this study could be considered expensive or difficult to learn, however the technology, by its nature, gets progressively smaller and cheaper, becoming more affordable for everyone.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the study is the small sample size; future study could replicate this contribution involving more participants with the aim of generalizing results to other countries and healthcare contexts as well. For example, a recent systematic review and meta-analysis by Parekh, Patel, Patel, and Shah [43] showed the relevant application of augmented reality also in the medical area. Similarly, Pulijala and colleagues [44] The technologies used in this study could be considered expensive or difficult to learn, however the technology, by its nature, gets progressively smaller and cheaper, becoming more affordable for everyone.…”
Section: Discussionmentioning
confidence: 99%
“…The final equation will give you a y-value for any x-value, not just those x and y values plotted with points. There are two types of least square regression: one is ordinary least square regression and the second is partial least square regression (PLSR) [45,46].…”
Section: Least Squaresmentioning
confidence: 99%
“…A relation identified by such an algorithm as the underlying source pattern is also referred to as stable, significant, or invariant. For our purposes, we will aim to demonstrate that our algorithms are statistically stable [45,46,50].…”
Section: Statistical Stabilitymentioning
confidence: 99%
“…Augmented reality (AR) and artificial intelligence (AI) have already grown into our daily lives, as we are used to playing AR games on our mobile phones and AI assists in facial recognition for serious or fun applications [ 141 ]. It is therefore just a matter of time, when AR and AI will be implemented into minimally invasive surgical procedures [ 142 ]. Three dimensional computer assisted laparoscopy or robotic surgery is an excellent platform for combining data from medical imaging, such as preoperative CT scans or intraoperative ultrasound, with the actual surgical field displayed to the surgeon in terms of augmented reality thereby displaying subsurface structures not visible to conventional laparoscopy [ 143 , 144 ].…”
Section: Reviewmentioning
confidence: 99%